STANDARD AGREEMENTS IN PROVIDING CREDIT BY BANKS TO CUSTOMERS AS SEEN FROM A CIVIL LAW PERSPECTIVE - Endang Hadrian; Dwi Atmoko; Jantarda Mauli Hutagalung (JILPR Journal Indonesia Law and Policy Review, 2026)
The banking sector in Indonesia plays a highly strategic role in the economy. Economic activity is a series of diverse legal acts. One of the most prominent forms of economic activity occurring in banking is the agreement between the customer as a consumer and the bank. Credit is currently in high demand among people with varying motives and consumption needs. Driven by increasingly pressing economic pressures, credit is an alternative way to obtain capital or funds needed for various community needs. Credit agreements granted by banks to customers are not without risk, as any risk may occur. The most common risk is the risk of failure or default in bank loan repayment. A new loan can only be issued after a written agreement has been reached between the debtor and the creditor, with the creditor acting as the lender and the debtor as the recipient of the loan. This written agreement is contained in a standard credit agreement. The credit agreement outlines the terms and procedures for applying for a loan with collateral and the obstacles in implementing the loan agreement. This research is an applied normative research with a descriptive approach. The problem-solving approach used is a normative juridical approach. The data used are primary and secondary data, consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In summary, a standard bank agreement is valid as long as it does not violate the law and maintains a balance between the rights and obligations of customers. The basis for this standard agreement is Article 1320 of the Civil Code.